1997
DOI: 10.1074/jbc.272.33.20929
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Highly Conserved Light Chain Shared by Dynein and Myosin V

Abstract: The M r 8,000 light chain originally identified in Chlamydomonas flagellar dynein is also a component of both cytoplasmic dynein and myosin V. Furthermore, this small protein has been implicated as an inhibitor of neuronal nitric oxide synthase, suggesting that it may play multiple regulatory roles within the cell. Covalent cross-linking of both dynein and myosin V using 1,5-difluoro-2,4-dinitrobenzene revealed that this light chain exists as a dimer in situ. This observation was confirmed using two additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
106
2
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 26 publications
9
106
2
2
Order By: Relevance
“…2B). LC8 alone showed a molecular mass of ϳ20 kDa, corresponding to a dimer and consistent with published data (39). Nek9 , with a predicted molecular mass of ϳ10 kDa, oligomerized with an apparent molecular mass of ϳ50 kDa.…”
Section: Lc8 Is Not Necessary For Nek9 Dimerization But Affects Nek9supporting
confidence: 72%
“…2B). LC8 alone showed a molecular mass of ϳ20 kDa, corresponding to a dimer and consistent with published data (39). Nek9 , with a predicted molecular mass of ϳ10 kDa, oligomerized with an apparent molecular mass of ϳ50 kDa.…”
Section: Lc8 Is Not Necessary For Nek9 Dimerization But Affects Nek9supporting
confidence: 72%
“…The function of DLC is regulated by PAK phosphorylation on DLC-Ser88 [157] that enhances endosomal trafficking and macropinocytosis [158]. Apart from its well known role as a component of dynein motors, DLC is also present as a stoichiometric subunit of the myosin V motors that transport short-range vesicles in the cell cortex [159,160] raising the possibility that PAK regulation of DLC function may affect traffic through both filament systems. Furthermore, like MP1/p14, LC8 (DLC1) also interacts with PAK1, a kinase that phosphorylates both MEK1 and LC8 [157].…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%
“…Therefore, it has been suggested that DLC1 could be involved in multiple cellular functions involving not only dynein but also several other proteins. Interestingly, a specific isoform in humans (DLC2) is shown to interact with myosin V but not dynein (Puthalakath et al, 2001) and an independent cell fractionation study with mouse brain extracts revealed that a large fraction of the cellular DLC1/LC8 proteins are not associated with micro- tubules (Benashski et al, 1997). Furthermore, a column pulldown assay that used the PIN/LC8 homologue revealed that this protein could interact with several isoforms of actin and dynamin-2 in rat brain lysate (Navarro-Lerida et al, 2004).…”
mentioning
confidence: 99%